2020
DOI: 10.1177/1741143220937312
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a research instrument for measuring the presence of democratic school leadership characteristics

Abstract: The main purpose of this article is to describe the process of development and validation of a research instrument for measuring the presence of democratic school leadership characteristics. The instrument has been developed and validated in the city of Zagreb and Zagreb County in Croatia in four phases: theoretical construction; expert validation ( N = 6 experts); pilot research ( N = 77 teachers); and instrument structure validation through the main research ( N = 651 teachers). The expert validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It can influence the motivation and performance of educators by creating the right mood and working environment, which significantly affects the quality of the school's outcomes [10]. Additionally, research has shown that a principal's management can have a considerable, albeit indirect, impact on students' academic performance [11][12][13]. The most important factor contributing to the…”
Section: Background To the Education Leadership And Its Impactmentioning
confidence: 99%
“…It can influence the motivation and performance of educators by creating the right mood and working environment, which significantly affects the quality of the school's outcomes [10]. Additionally, research has shown that a principal's management can have a considerable, albeit indirect, impact on students' academic performance [11][12][13]. The most important factor contributing to the…”
Section: Background To the Education Leadership And Its Impactmentioning
confidence: 99%
“…Validity is the extent to which the measuring instrument (test) truly describes what is intended to be measured. There are three types of validity, namely content validity (content validity), criterion validity (criteria validity), and construct validity (concept validity) (Pažur, 2020). Content validity is carried out to ensure whether the contents of the questionnaire are appropriate and relevant to the study objectives (Ihsan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The currently dominant views of 'democratic education' have revolved around educating students in the values associated with democracy, such as freedom, equality, participation, and social justice (Gutmann and Ben-Porath 2015;Rata 2020;Yates 1999). Standardised assessment tools have even been developed to measure how 'democratic' an educational practice is, based on the enactment of those values in the classroom (e.g., Pažur 2022;Shechtman 2002). Exemplary evidence can be seen, for instance, in an encyclopaedia entry entitled 'democratic education' by Gutmann and Ben-Porath (2015) which provides an overview of the key concepts and current debates on the topic.…”
Section: Introductionmentioning
confidence: 99%